2014
DOI: 10.1109/tdsc.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Remote Physical Device Fingerprinting”

Abstract: On the Use of the ISBAS Acronym in InSAR Applications. Comment on Vajedian, S.; Motagh, M.; Nilfouroushan, F. StaMPS Improvement for Deformation Analysis in Mountainous Regions: Implications for the Damavand Volcano and Mosha Fault in Alborz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…en, Polcak validated Kohno's technology again in 2014, which shows that the method is suitable for the computer identification [32]. Identifying a device through these hardware does have a good performance.…”
Section: Related Workmentioning
confidence: 93%
“…en, Polcak validated Kohno's technology again in 2014, which shows that the method is suitable for the computer identification [32]. Identifying a device through these hardware does have a good performance.…”
Section: Related Workmentioning
confidence: 93%
“…To the best of our knowledge, we are the first to report on the privacy aspects of the TFO protocol. While research work on privacy issues within TCP that allows distinguishing clients or servers based on their TCP timestamps [17,22] exists, our reported storage-based tracking mechanism is unrelated to such tracking approaches via the TCP timestamps. A similar tracking mechanism has been reported for the QUIC transport protocol [30].…”
Section: Related Workmentioning
confidence: 99%
“…In the field of network traffic analysis, researchers devote to extracting attributes from network traffic to identify the device or users even though the device IP changes. In the physical layer, Polcak et al [17] proposed a kind of attribute to identify computers by their clock skew computed from TCP timestamps. In the operating system layer, Franklin and McCoy [18] found that the 802.11 probe request time interval can reveal the active scanning algorithms employed by wireless derivers.…”
Section: Related Workmentioning
confidence: 99%